Biscuit packaging and storage. packaging materials, wrapping operations, biscuit storage, troubleshooting tips - Manley, Duncan (Woodhead Publishing, 1998)
The final manual describes the range of packaging options available together with storage and handling, highlighting the key issues in retaining product quality.